Ameliorative Activity of Vitamin C against Alcohol Induced Cardio-toxicity in Adult Male Wistar Rats - Olusoji Oyesola; Peter Okhiai; Sunday Adenekan; Ifedolapo Owoeye; Emmanuel Taiwo George (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlights: 1. Ameliorative effects of vitamin C against alcohol in this research are very interesting to be observed. 2. Vitamin C may have some beneficial effects on heart function by acting as an antioxidant. - Background: Alcohol and it metabolites causes cardiomyopathy, which is one of the main form of alcohol induced heart damage. The aim of the present study was to investigate the protective effect of vitamin C against alcohol-induced heart toxicity and selected indices. Material and Methods: Forty healthy male Wistar rats were used in this experiment, which lasted 21 days. The rats were divided into eight groups, with five rats in each group. Group A received only distilled water, Group B received 6000 mg/kg of alcohol, and Groups C to H received different doses of vitamin C and alcohol in varying combinations. Blood samples were collected and analyzed for levels of sodium, potassium, and chloride ions. The hearts were also analyzed for antioxidant activities and histo-pathological changes. Results: The findings indicated that alcohol administration caused a decrease in blood electrolyte levels compared to the control group, while treatment with vitamin C and co-administration of vitamin C and alcohol improved blood electrolyte levels. The antioxidant enzymes activity of the heart improved in the vitamin C and co-administration groups, as evidenced by increased GSH, SOD, and CAT activity and decreased MDA levels when compared to the alcohol-only group. Conclusion: Therefore, this study suggests that commercial grade vitamin C at doses of 100 mg/kg, 200 mg/kg, and 300 mg/kg can protect the heart against alcohol-induced toxicity. However, further research is necessary to examine the anti-inflammatory effect of commercial grade vitamin C.